THE EMPIRICAL-NORMATIVE DICHOTOMY IN LEGAL STUDIES (AN ANALYSIS OF THE CLAIM OF SUI GENERIS LEGAL SCIENCE) - Pamujiningsih , Ulfia; Priyono, Joko (The Officium Nobile Journal, 2025)
The debate regarding the legal status of law as a science remains an important issue in legal studies, especially in relation to the dichotomy between normative and empirical approaches in legal research. This study aims to analyze the character of legal science as a unique discipline (sui generis) and the relevance of integrating normative and empirical approaches in the development of legal science in Indonesia. Legal research in accordance with scientific requirements does not only stop at describing legal analysis as a sui generis science, but also the need to understand the controversies that arise, namely the assumption that legal science is a branch of other disciplines, as well as looking at the background of legal studies based on philosophical schools of thought. The research methodology used is normative legal research with a concept-based approach. The findings show that legal science has a distinctive scientific structure, consisting of legal dogmatics, legal theory, and legal philosophy, thereby confirming the position of law as an autonomous science. Legal studies reveal a dichotomy between legal research and empirical legal research, which should not be considered contradictory. This dichotomy is understood as a complementary relationship that reflects the uniqueness of law as a sui generis discipline that is both prescriptive and descriptive in nature.